Frequency and histopathological classification of canine mastocytoma in the casuistry (period 2000-2006) of a histopathology veterinary laboratory in Lima, Peru - Heredia N., Ronald (2015)
The aim of this retrospective study was to classify mastocytomas according to histologic grade from samples of canine necropsies and biopsies diagnosed by histopathology in the Pathology Laboratory of the Faculty of Veterinary Medicine of the National University of San Marcos, Lima, Peru in the period 2000-2006. A total of 40 cases of mastocytomas were found (4.5%) in 881 neoplasms. The classification of the mastocytomas based on the histologic grade indicated that el 42.5% were of grade I (well differentiated), 47.5% of grade II (moderately differentiated) and 10% of grade III (poorly differentiated). Moreover, 63.9% (23/36) cases were found in the Boxer breed.